(untitled) (Applied Biological Research, 2012)
A total of 634 canines were sampled for both haematological (460) and coprological (174) investigations at Small Animal Clinics, GADVASU, Ludhiana, India during the year 2010. Examination of Giemsa stained peripheral blood smears exhibited 10.21% (47/460) haemoprotozoan comprizing of Babesia gibsoni (8.26%), Hepatozoon canis (1.08%), B. canis (0.65%) and Trypanosoma evansi (0.21%). B. gibsoni infection was significantly higher (p<0.05) in male dogs. Coprological examination revealed that the prevalence of gastro-intestinal parasitic infection was 24.71% (43/174). Among these Isospora spp. and Ancylostoma spp. were 2.29 and 22.41%, respectively. The present work emphasized that B. gibsoni and hookworms were most prevalent blood- and gastro-intestinal parasites in canines in and around Ludhiana, Punjab (India).